2019
DOI: 10.1007/s00394-019-02073-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spirulina and wakame consumption on intestinal cholesterol absorption and serum lipid concentrations in non-hypercholesterolemic adult men and women

Abstract: Purpose Consumption of the algae spirulina (Arthrospira platensis or maxima) and wakame (Undaria pinnatifida) has been shown to lower LDL cholesterol concentrations in animals and humans, possibly due to the inhibition of intestinal cholesterol absorption. This mechanism, however, has never been investigated in humans. Therefore, we examined in nonhypercholesterolemic men and women the effects of spirulina and wakame consumption on serum markers for intestinal cholesterol absorption. Methods Thirty-five health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…This review included 18 RCTs, from which 12 had a crossover design [27][28][29][30][31][32][33][34][35][36][37][38] and 6 had a parallel design. [39][40][41][42] Of the 18 studies, 10 28,29,32-35 involved an acute intervention as an oral glucose tolerance test (OGTT), measuring the intervention's effect on PPG over 2 to 3 h. Five studies 27,30,[40][41][42] conducted only long-term interventions analyzing the effect on FPG. The remaining 3 [39][40][41] reported on both FPG and PPG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review included 18 RCTs, from which 12 had a crossover design [27][28][29][30][31][32][33][34][35][36][37][38] and 6 had a parallel design. [39][40][41][42] Of the 18 studies, 10 28,29,32-35 involved an acute intervention as an oral glucose tolerance test (OGTT), measuring the intervention's effect on PPG over 2 to 3 h. Five studies 27,30,[40][41][42] conducted only long-term interventions analyzing the effect on FPG. The remaining 3 [39][40][41] reported on both FPG and PPG.…”
Section: Resultsmentioning
confidence: 99%
“…In all the included studies, a placebo was used as a control comparator (Table 2). [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The study populations ranged from 12 to 97 participants. Ten studies [29][30][31][32][33][34][35][36][37][38] were conducted on healthy participants (n ¼ 256) with a normal FPG (<100 mg/dL) and BMI (18.5 and 24.9 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have reported conflicting outcomes regarding the efficacy of spirulina on blood pressure. 46,47 van den Driessche et al 46 indicated that a daily intake of 4.8 g spirulina did not affect SBP or DBP among non-hypercholesterolemic adults.…”
Section: Ta B L Ementioning
confidence: 99%
“…This alga and its extracts are believed to have many functions as antioxidant and anti-inflammatory properties [104]. Many Spirulina products, now available as super-food/herbal supplements to reduce cholesterol concentration by reducing triacylglycerols level [105], through research on rabbit confirm this characteristic [106], while more recent research on a human claim no changes were made after consuming Spirulina on cholesterol profile [107]. More research on human lipid profile behaviour after spirulina consumption is highly recommended.…”
Section: Nutraceuticals From the Algal And Cyanobacterial Originmentioning
confidence: 99%